2017
DOI: 10.1111/jdi.12641
|View full text |Cite
|
Sign up to set email alerts
|

Association between poor psychosocial conditions and diabetic nephropathy in Japanese type 2 diabetes patients: A cross‐sectional study

Abstract: Aims/IntroductionIt is suggested that a positive psychosocial condition has a good effect on health and glycemic control. However, there has been no research to evaluate the association between positive psychosocial factors and diabetic nephropathy (DN). The aim of the present study was to evaluate the association between psychosocial factors and DN in patients with type 2 diabetes.Material and MethodsTo assess psychosocial condition, six indicators (happiness score, Life Orientation Test‐revised score as an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 43 publications
2
8
0
Order By: Relevance
“…When the social support model entered the model, R c 2 rose highest, from 0.245 to 0.540, which means social support was the most important factor in the final model. This result is similar to the study results of Ninomiya et al (Ninomiya et al., 2018 ) and Vassilev et al (Vassilev et al., 2016 ) on adults with diabetes. We believe that social support is an important factor to the social network of adults with diabetes of all ages.…”
Section: Discussionsupporting
confidence: 92%
“…When the social support model entered the model, R c 2 rose highest, from 0.245 to 0.540, which means social support was the most important factor in the final model. This result is similar to the study results of Ninomiya et al (Ninomiya et al., 2018 ) and Vassilev et al (Vassilev et al., 2016 ) on adults with diabetes. We believe that social support is an important factor to the social network of adults with diabetes of all ages.…”
Section: Discussionsupporting
confidence: 92%
“…The observed sex difference may be due to different coping strategies between men and women. Furthermore, a Japanese study observed that higher levels of social support and a highly connected social network was associated with a lower prevalence of diabetic nephropathy [ 22 ].…”
Section: Social Network and Diabetes Complicationsmentioning
confidence: 99%
“…In women, small network and less informational support is associated with microvascular complications (ORs 1.02–1.71). Ninomiya (2018) [ 22 ] Study name: NA. T2D from general population, Osaka (Japan).…”
Section: Social Network and Diabetes Complicationsmentioning
confidence: 99%
“…Recently, the relationship between health status and psychosocial factors, including psychological aspects and level of social support, has been discussed (34). Optimism is associated with a decrease in mortality from cardiovascular disease and coronary heart disease, lower rates of nonfatal myocardial infarction, and slowing down the progression of atherosclerosis of the carotid arteries (35).…”
Section: Discussionmentioning
confidence: 99%